Oxidosqualene cyclase and CYP716 enzymes contribute to triterpene structural diversity in the medicinal tree banaba. Issue 1 (20th December 2018) - Sandeep,; Misra, Rajesh Chandra; Chanotiya, Chandan Singh; Mukhopadhyay, Pradipto; Ghosh, Sumit
Summary: Pentacyclic triterpenes (PCTs) represent a major class of bioactive metabolites in banaba ( Lagerstroemia speciosa ) leaves; however, biosynthetic enzymes and their involvement in the temporal accumulation of PCTs remain to be studied. We use an integrated approach involving transcriptomics, metabolomics and gene function analysis to identify oxidosqualene cyclases (OSCs) and cytochrome P450 monooxygenases (P450s) that catalyzed sequential cyclization and oxidative reactions towards PCT scaffold diversification. Four monofunctional OSCs (LsOSC1, 3–5) converted the triterpene precursor 2, 3‐oxidosqualene to either lupeol, β‐amyrin or cycloartenol, and a multifunctional LsOSC2 formed α‐amyrin as a major product along with β‐amyrin. Two CYP716 family P450s (CYP716A265, CYP716A266) catalyzed C‐28 oxidation of α‐amyrin, β‐amyrin and lupeol to form ursolic acid, oleanolic acid and betulinic acid, respectively. However, CYP716C55 catalyzed C‐2α hydroxylation of ursolic acid and oleanolic acid to produce corosolic acid and maslinic acid, respectively. Besides, combined transcript and metabolite analysis suggested major roles for the LsOSC2, CYP716A265 and CYP716C55 in determining leaf ursane and oleanane profiles. Combinatorial expression of OSCs and CYP716s in Saccharomyces cerevisiae and Nicotiana benthamiana led to PCT pathway reconstruction, signifying the utility of banaba enzymes for bioactive PCT production in alternate plant/microbial hosts that are more easily tractable than the tree species.